The Knowledge and Attitude Regarding Hazards of Tobacco Chewing among People of Early Adulthood at Selected area, Jaipur - Avinash Choudhary; Prakash Babulal Sharma; Prakash Salvi (International Journal of Medical Research and Review, 2022)
Introduction: Healthy habits are a vital role to survive for long period even, such as eating well,avoiding harmful substances, exercising and yoga etc. Second-hand smoke (SHS) has two maincomponents, sidestream and mainstream smoke. Non-smokers can get affected by breathing incigarette smoke at home and in other areas outside home..Material and methods: It isdescriptive non-experimental study carried out among the mothers of under-five children atSPMCHI, Jaipur city (Rajasthan). Study was conducted in year 2020 and 60 mothers under-fivechildren were selected by using purposive non-probability sampling method. A pilot study wasperformed on 10 mothers of under-five children to test reliability and feasibility of study. Reliabilityof knowledge tool was conducted through Kuder and Richardson Formula 20 (KR20) result was 0.72and reliability of 5 point rating scale was analyzed by using the Cronbach alfa method it was 0.89.Results: Level of knowledge mothers of under-five children, which 60% (36) had poor knowledge,25% (15) had average knowledge and 15% (9) had good knowledge regarding impact of passivesmoking. Level of attitude of mothers under-five children, that 20% (12) had an unfavourableattitude, 67% (40) had neutral attitude, and 13% (8) had favourable attitude. It evidenced that forcorrelation between knowledge and attitude calculated value of Karl Pearson’s correlation coefficientis 0.11 and tabulated value of correlation coefficient is 0.250 for df 58 at 0.05 level ofsignificance.Conclusion: Present study reveals most of socio-demographic variables indicate asignificant association with level of knowledge regarding impact of passive smoking among mothersof under-five children except age and smoking habit of family member.